Tradisi Matrilineal dalam Tjoerito Parasaian Me’saleh - Ka'bati Ka'bati (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
This article discusses the neglect of matrilineal tradition by Pariaman society during the colonial era (1846-1922), based on a study of autobiography written by Me’ Saleh gala Datoe’ Oerang Kajo Basa. The book entitled Tjoerito Parasaian Me’ Saleh is a family historical note of successful trader in Pariaman. The society in Pariaman is known as heterogeneous in terms of ethnicity, cultures, and religion, in contrast to darek society that is known as homogeneous in the mentioned fields. The heterogeneity of the Pariaman society then forms a social relational pattern and it is a different form compared to the darek society. The autobiography illustrates that the cultural characteristics of Pariaman society in the beginning was formed by their interaction with foreign people from Aceh, Nias, Bugis, India, China, Madura, Arab, and European countries. Since then they became an open minded people and easy to adapt with new influences. This condition resulted some matrilineal tradition applied in darek was not implemented and obeyed in rantau.